PENGUKURAN KINERJA MESIN DEFEKATOR I DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS(Studi Kasus pada PT. Perkebunan XY ) - Saiful, Saiful; Rapi, Amrin; Novawanda, Olyvia (JEMIS (Journal of Engineering & Management in Industrial System), 2014)
It takes a good maintenance management at any company to be able to run the production process effectively and efficiently. However, in practice often attempt maintenance or repair only be a waste, because the maintenance team does not know clearly the problems that occur and the factors. The purpose of this study was to measure the value of Overall Equipment Effectiveness (OEE), determine the magnitude of each factor of six big losses that affect the effectiveness of the defekator I machine, and an analysis of the factors that a top priority as the basis for repairs. In this study the method used Overall Equipment Effectiveness (OEE), and OEE six big losses to measure the performance of the machine for six months and to determine the factors of the six factors in the six big losses that give the most impact on the effectiveness of the defektor I machine. Based on the results of data processing, Overall Equipment Effectiveness value defekator I machine in purification station PT. PerkebunanÂ  XY, the ideal situation is achieved only in August and October with OEE value of 85.53% in August and 85.29% in October. Meanwhile, in June, July, September, and November OEE values are respectively 84.87%, 80.47%, 84.63%, and 76.89%. The results of the calculation of the six big losses, it is known that loss and rework loss breakdown is a factor with the largest percentage for the low effectiveness of the defekator I machine with a percentage of 63.57% for the breakdown loss and rework a loss of 24.23%. OEE and OEE value of six big losses are the basis for the provision of the proposed improvement.